A prospective randomised comparison of fixation methods in Tamai's zone I amputation. Issue 7 (July 2018) - Shim, Hyung-Sup; Kwon, Byung Yeun; Seo, Bommie F.; Kwon, Ho; Jung, Sung-No
Summary: Background: The treatment of choice for fingertip amputation is replantation to restore function and aesthetics. The purpose of this study was to compare the success rates and salvage periods between patients with Tamai's zone I amputation injuries treated with bony fixation and suture fixation. Methods: Fifty-five patients with Tamai's zone I amputations with bony involvement were included in this study. The patients were allocated randomly to two groups treated by bony fixation with Kirschner (K-)wire and suture fixation, respectively. In the bony fixation group ( n  = 21), the distal phalangeal bone was fixed with K-wire; in the suture fixation group ( n  = 34), the amputated portion was fixed with sutures alone. The success rate was defined as the percentage of fully viable replanted cases, and the salvage period was defined as extending from the first postoperative day to the cessation of salvation. Results: The success rates for the bony and suture fixation groups were 90.0% and 91.1%, respectively, with no significant difference. The average salvage period was longer in the bony fixation group than in the suture fixation group (8.7 ± 1.25 vs . 6.4 ± 0.98 days; P  = 0.01). No case of non-union of the distal phalangeal bone, limitation of motion, or disfigurement was observed in either group. Conclusion: The average salvage period was significantly longer for the bony fixation group, but the success rates did not differ between groups. We suggest that bony fixation is not mandatory in the treatment of Tamai's zone I amputation.